EPIDEMIOLOGICAL ANALYSIS OF LEPROSY (HANSEN'S DISEASE) IN THE MUNICIPALITY OF ANÁPOLIS – GOIÁS (CIPEEX, 2025)
Leprosy is a chronic infectious disease caused by M. leprae. It is a disease of high infectivity and low pathogenicity, characterized by hypochromic or reddish patches associated with reduced local sensitivity. Regarding the pattern of this disease in Brazil, there are few studies on leprosy in the municipality of Anápolis. Thus, the present study aims to analyze epidemiological data related to leprosy infection in the city of Anápolis, Goiás. This is a quantitative, descriptive, observational, and cross-sectional study conducted in Anápolis, at the Municipal Health Department - Dr. Ilion Fleury Jr. Health Unit. Data were collected systematically, taking into account gender, age group, and home address. The analysis focused on describing and interpreting the available data, with an emphasis on identifying trends and general patterns. Regarding the results of the study, the data reveal a predominance of cases among men, with the most affected age group being between 50 and 64 years old. Data on the patients' place of residence show that leprosy cases are spread across several neighborhoods in Anápolis, with no concentration in a single area. Thus, in conclusion, the data can guide public policies and improve leprosy control, with an emphasis on early diagnosis, adequate treatment, and reduction of social stigma.
Keywords: Mycobacterium leprae; Leprosy; Hansen's disease; Hanseniasis